2018
DOI: 10.1017/s0144686x18001022
|View full text |Cite
|
Sign up to set email alerts
|

Larger Chinese text spacing and size: effects on older users’ experience

Abstract: With declining vision ability, character spacing and size on smartphones designed for the general population are not accessible for older adults. This study aimed to explore how larger Chinese character spacing and size affect older adults’ user experience (UX). An orthogonal experiment was conducted. The optimal range of font size (FS), word spacing (WS) and line spacing (LS) were proposed utilising subjective evaluations to investigate the correlation of eye movement data with participants perceived UX. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…The lighting in the experiment environment is an essential factor that affects productivity. Some studies simulated environmental lighting in their experiment to observe the effect on reading time/speed, readability and legibility of font sizes (Yeh, 2020 ) performed their experiment in a classroom to minimize outside inference, sunlight was adequate, and minimal noise and a controlled temperature of 26 degrees C. Another study by Hou et al ( 2020 ) simulated ambient lighting using 40-Watt LED lights during the experiment. Although the direct effect of the environmental factors was not explored, we can conclude that the experiment's environment influences the size recommendations in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lighting in the experiment environment is an essential factor that affects productivity. Some studies simulated environmental lighting in their experiment to observe the effect on reading time/speed, readability and legibility of font sizes (Yeh, 2020 ) performed their experiment in a classroom to minimize outside inference, sunlight was adequate, and minimal noise and a controlled temperature of 26 degrees C. Another study by Hou et al ( 2020 ) simulated ambient lighting using 40-Watt LED lights during the experiment. Although the direct effect of the environmental factors was not explored, we can conclude that the experiment's environment influences the size recommendations in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that increasing both the Chinese inter-character spacing and inter-line spacing significantly improved reading performance for older adults. In a study by Hou et al ( 2020 ) investigating the effect of Chinese text spacing and size on older user experience, the effects on usability, visual comfort, cognitive load and reading performance were explored. An eye tracker was used to obtain eye movement data which was then analyzed.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with digital reading, traditional books help protect eyesight and are less dependent on computers ( Jeong, 2012 ; Hou et al, 2020 ). More people have in recent years become addicted to digital reading, whether adolescents ( Lee et al, 2014 ) or adults ( Elhai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%